Synthesis, Screening and Characterization of Novel Potent Arp2/3 Inhibitory Compounds Analogous to CK-666 - Fokin, Artem I.; Chuprov-Netochin, Roman N.; Malyshev, Alexander S.; Romero, Stéphane; Semenova, Marina N.; Konyushkin, Leonid D.; Leonov, Sergey V.; Semenov, Victor V.; Gautreau, Alexis M. (Frontiers in Pharmacology, 2022)
Branched actin networks polymerized by the Actin-related protein 2 and 3 (Arp2/3) complex play key roles in force generation and membrane remodeling. These networks are particularly important for cell migration, where they drive membrane protrusions of lamellipodia. Several Arp2/3 inhibitory compounds have been identified. Among them, the most widely used is CK-666 (2-Fluoro-N-[2-(2-methyl-1H-indol-3-yl)ethyl]-benzamide), whose mode of action is to prevent Arp2/3 from reaching its active conformation. Here 74 compounds structurally related to CK-666 were screened using a variety of assays. The primary screen involved EdU (5-ethynyl-2'-deoxyuridine) incorporation in untransformed MCF10A cells. The resulting 9 positive hits were all blocking lamellipodial protrusions and cell migration in B16-F1 melanoma cells in secondary screens, showing that cell cycle progression can be a useful read-out of Arp2/3 activity. Selected compounds were also characterized on sea urchin embryos, where Arp2/3 inhibition yields specific phenotypes such as the lack of triradiate spicules and inhibition of archenteron elongation. Several compounds were filtered out due to their toxicity in cell cultures or on sea urchin development. Two CK-666 analogs, 59 (N-{2-[5-(Benzyloxy)-2-methyl-1H-indol-3-yl] ethyl}-3-bromobenzamide) and 69 (2,4-Dichloro-N-[2-(7-chloro-2-methyl-1H-indol-3-yl) ethyl]-5-[(dimethylamino) sulfonyl] benzamide), were active in all assays and significantly more efficient in vivo than CK-666. These best hits with increased in vivo potency were, however, slightly less efficient in vitro than CK-666 in the classical pyrene-actin assay. Induced-fit docking of selected compounds and their possible metabolites revealed interaction with Arp2/3 that suppresses Arp2/3 activation. The data obtained in our screening validated the applicability of original assays for Arp2/3 activity. Several previously unexplored CK-666 structural analogs were found to suppress Arp2/3 activation, and two of them were identified as Arp2/3 inhibitors with improved in vivo efficiency.